Post-transfusion Hepatitis Following the Use of Prothrombin Complex Concentrates - Roberts, Harold R; Blatt, Philip M (Thrombosis and Haemostasis, 1975)
The incidence of post-transfusion hepatitis in patients receiving concentrates containing the prothrombin complex factors is reviewed. A survey of the literature indicates a high incidence of hepatitis in such patients.